ANALISIS PERBANDINGAN PENERIMAAN PAJAK PENGHASILAN (PPH) WAJIB PAJAK ORANG PRIBADI SEBELUM DAN SESUDAH KENAIKAN PENGHASILAN TIDAK KENA PAJAK PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA MALANG SELATAN - Devita Jeniliasari; Jeni susyanti; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
Abstract This study analyzes the comparison of income tax payments of individual taxpayers before and after changes in income that are not taxable with research data for the year 2012-2018. This research was conducted in KPP Pratama Malang Selatan. The purpose of this study is (1) to analyze the comparison of tax revenues before and after the increase in non-taxable income (PTKP) (2) to analyze the comparison of the number of taxpayers before and after the increase in non-taxable income (PTKP). The research of this paper uses analytical techniques such as comparative analysis. The data needed in this study are the amount of tax revenue, the number of taxpayers, and the list of non-taxable income, for the past seven years. The analytical method used is Statistical Product and Service Solutions (SPSS) version 2.1. The analytical method used in this study includes descriptive statistics, normality tests, hypothesis testing. The results of this study indicate that the amount of tax revenue is different but not significant before and after the change in income is not taxable. While the number of taxpayers shows that there are differences in the number of taxpayers before and after changes in income are not taxable. The existence of a difference in the form of an increase in the number of taxpayers before and after changes in non-taxable income (PTKP) can be due to an increase in income not taxable will result in a decrease in the level of tax revenue. Keywords: Tax revenue, taxpayer, non-taxable income (PTKP).